A scoping review of olfactory interventions for fatigue relief: addressing occupational health hazards - Jiang, Xinyue; Muthusamy, Kanesan; Fang, Xueliang (Frontiers in Public Health, 2024)
Background Fatigue poses risks to occupational health and safety, affecting individuals' work efficiency, physical health, and social security, as well as human wellbeing and quality of life. Olfactory interventions, due to their low interference, are considered promising strategies for mitigating fatigue and reducing occupational health hazards. Objective The objective of this review is to bridge the current gaps in the literature by conducting a scoping review of olfactory interventions on human alertness. It aims to explore their application in various occupational settings and to provide comprehensive and practical guidance for the practical application of olfactory interventions in mitigating fatigue and reducing occupational risks. Methods The literature research was conducted in English using electronic databases such as Web of Science. Keywords related to scent and fatigue and the review followed PRISMA Extension for Scoping Reviews and PICO framework. Results 28 studies were included in this work. Participant characteristics, fatigue measurement methods, and scent intervention methods, such as types of scents, intervention strategies, and scent presentation systems, are thoroughly investigated and discussed. Additionally, the study places a specific emphasis on the applications and research within the field of scent interventions for fatigue driving. Olfactory interventions have been applied to populations in various occupational fields, demonstrating beneficial effects on both physiological and psychological fatigue. Conclusions Olfactory intervention is effective and promising for enhancing alertness and improving the occupational environment. To provide detailed and practical guidance for the actual application of olfactory intervention in fatigue relief and reducing occupational health and safety hazards, further research into the potential mechanisms, applications, and efficacy assessment systems of fatigue-related olfactory interventions is necessary.